DEVELOPMENT TRENDS OF THE GLOBAL TEXTILE INDUSTRY: A COMPREHENSIVE ANALYSIS (Scientific Journal of Actuarial Finance and Accounting, 2024)
The textile industry, a cornerstone of global manufacturing, has witnessed significant transformation over the years driven by technological advancements, shifting consumer preferences, and global economic dynamics. This paper provides a comprehensive analysis of the development trends shaping the global textile industry. It examines key drivers such as technological innovation, sustainability initiatives, market demand shifts, circular economy practices, and geopolitical factors, and explores their implications for industry players. Additionally, the paper discusses emerging trends including digitalization, supply chain optimization, and the rise of smart textiles. By synthesizing insights from industry reports, academic research, and expert opinions, this paper offers valuable perspectives on the future trajectory of the global textile industry. Furthermore, embracing principles of sustainability and circular economy in textile production and consumption can pave the way for a more resilient and environmentally responsible industry. By optimizing resource utilization, minimizing waste, and prioritizing ethical and sustainable practices, the textile industry can contribute positively to economic growth, social development, and environmental stewardship on a global scale.